Pengaruh Ekspektasi Kinerja, Ekspektasi Upaya, Kondisi yang Memfasilitasi dan Kepercayaan terhadap Penggunaan Aplikasi investasi IPOT - Mufidha Riska; Rahmawati Khoiriyah; Budy Prihastoro (Scimadly Publishing, 2024)
The era of advances in information technology has caused a shift in business operations towards digital platforms, including the capital market. Capital market transactions on the Indonesia Stock Exchange (BEI) can be done online via the IPOT platform. In Indonesia the IPOT platform is the most popular application. The aim of this research was to measure behavior in using the IPOT application using the UTAUT approach. Using multiple linear regression analysis with a population of 3rd semester Faculty of Economics and Business students with a sample of 86 respondents taken with the criteria of having opened an account or used the IPOT investment application. The research results state that partially the variables of performance expectations and trust influence behavior in using the IPOT investment application. Meanwhile, business expectations and facilitating conditions have no effect on behavior in using the IPOT investment application.